The role of private and institutional support to favor work-family integration in pre-service and in-service teachers: Self-related vs. context-related arguments - Arcidiacono, Francesco; Bova, Antonioa; Ben-Uri, Ina; Melfi, Giuseppe (Swiss Journal of Educational Research, 2022)
Research related to the integration of the demands of work and family highlights the difficulties teachers experience in handling their careers and private lives. The goal of this study is to examine the arguments they use to explain what might make work-family integration easier for them. A questionnaire has been administered to 728 teachers in Israel and Switzerland, two countries dealing with teachers’ work-family relations. Through a qualitative analysis of the types of arguments advanced by teachers, the reconstruction of their reasoning (for the topical and endoxical components) has been performed. Results reveal that the support of family and institution are advanced as critical aspects in both countries. Implications in shaping teachers’ attitudes towards work-family integration are discussed.